The Ideal and Reality of Election Law Enforcement in Indonesia - Uu Nurul Huda; M Yahya Wahyudin (Law Development Journal, 2026)
Elections are a cornerstone of democracy as well as a mechanism for the distribution of power and political accountability in Indonesia. The enforcement of laws against election violations determines the extent to which the principles of direct, universal, free, secret, honest, and fair elections are truly realized in practice. This article aims to analyze the gap between the ideal norms of election law enforcement and the empirical reality of their implementation following the reform era. The research employs a normative-empirical legal methodology through the study of legislation, institutional design, court rulings, official election oversight data, and an examination of several representative cases of violations. The findings indicate that Indonesia has established a relatively comprehensive regulatory and institutional framework through the KPU, Bawaslu, DKPP, and Sentra Gakkumdu to govern the regime of administrative, ethical, and criminal sanctions. However, the effectiveness of law enforcement, particularly regarding criminal election violations, remains weak and tends to be symbolic. Three main factors hindering this are the lack of clarity regarding norms and standards of proof, fragmented inter-institutional coordination, and a permissive political culture that tolerates repeated violations. This article concludes that there is a need to refine regulations, strengthen institutional capacity and enforcement coordination, and prioritize political education and voter legal literacy to reinforce electoral integrity and electoral justice in Indonesia. Normative recommendations include simplifying the formulation of electoral criminal offenses, increasing investigative resources, and expanding access to electoral justice mechanisms for citizens. These findings are expected to contribute to academic debate and the future agenda for electoral regulatory reform.